Effect of Steaming and Boiling on the Antioxidant Properties and Biogenic Amines Content in Green Bean (Phaseolus vulgaris) Varieties of Different Colours. (12th January 2017) - Preti, Raffaella; Rapa, Mattia; Vinci, Giuliana
Abstract : Effects of boiling and steaming cooking methods were studied on total polyphenols, antioxidant capacity, and biogenic amines of three green bean varieties, purple, yellow, and green. The vegetables gave good values both for antioxidant capacity and for phenolics content, with the purple variety being the richest in healthful components. Both the heat treatments affected the antioxidant properties of these vegetables, with boiling that reduced the initial antioxidant capacity till 30% in the yellow variety, having the same trend for total polyphenols, with the major decrement of 43% in the green variety. On the contrary, biogenic amines significantly increased only after boiling in green and yellow variety, while purple variety did not show any changes in biogenic amines after cooking. The steaming method showed being better cooking approach in order to preserve the antioxidant properties of green beans varieties and to maintain the biogenic amines content at the lowest level.